Molecular Phylogeny of the Ant Subfamily Formicinae (Hymenoptera, Formicidae) from China Based on Mitochondrial Genes - Zhilin Chen (Universidade Estadual de Feira de Santana, 2013)
To resolve long-standing discrepancies in the relationships among genera within the ant subfamily Formicinae, a phylogenetic study of Chinese Formicine ants based on three mitochondria genes (Cyt b, COI, COII) was conducted. Phylogenetic trees obtained in the current study are consistent with several previously reported trees based on morphology, and specifically confirm and reinforce the classifications made by Bolton (1994). The tribes Lasiini, Formicini, Plagiolepidini and Camponotini are strongly supported, while Oecophyllini has moderate support despite being consistent across all analyses. We have also established that the genus Camponotus and Polyrhachis are indeed not monophyletic. Additionally, we found strong evidence for Polyrhachis paracamponota, as described by Wu and Wang in 1991, to be corrected as Camponotus based on molecular, morphological and behavioral data.